Qualitative study of how care is planned and delivered to people living with dementia and a long‐term condition. (1st February 2022) - Rees, Jessica; Walters, Kate; Burton, Alexandra; Cooper, Claudia
Abstract: Background: Dementia rarely travels alone. In the UK, almost 8 in every 10 people with dementia have another chronic condition. Long‐term conditions require continuous management in primary care, including support for self‐management. Tailoring physical health care plans to account for dementia is vital and requires skill and confidence from health care professionals. The objective of this study was to understand how care is planned in primary care, and how professional advice is followed at home, when a person has dementia and a long‐term condition. Method: We conducted a remote ethnographic study, beginning in September 2020, using qualitative interviews, participant observations supplemented by care plan document analysis and event‐based diaries. We invited people with dementia and their family carers, and relevant health and social care professionals and/or home care workers involved in care of long‐term conditions to participate. We used inductive thematic analysis to analyse observations and interviews and integrated the findings with document analysis to ensure data triangulation. Result: Preliminary findings indicate a degree of disconnect between participant account of health care and documented medical notes, specifically between the 'goal setting' and 'action planning' aspects of care planning. Participants discussed the impact of the pandemic and reduced physical contact with primary care; in addition to aspects of holistic health management such as the closure of swimming pools. We consider how relationships between participants and general practitioners, homecare workers, and pharmacists are constructed within the care networks of people living with dementia and how these have shifted during the pandemic. We will present our reflections on conducting remote observations with people with dementia, including challenges of developing trust over the phone and overcoming technology barriers. Conclusion: Continued involvement of people with dementia in healthcare and in research is imperative despite the challenges of remote contact. Special consideration is required for people with dementia who lack capacity to ensure proxy management by family or home care workers does not become primary management.